The influence of demographics and sustainable “net zero” transition on the demoeconomic quality of life in the implementation of “Demoethics” values - Zhanbayev, R.A.; Maksimov, D.G.; Sagintayeva, S.S.; Madenova, A.E.; Tansykbayeva, G.O.; Kalabayev, N.B. (BUKETOV BUSINESS REVIEW, 2024)
Object: The goal of the work is to develop components of demoeconomics based on the value of demoethics that contribute to the achievement of sustainable development goals, which stipulates their consideration in the context of the influence of demographic processes and the transition to “net zero”. Methods: A systematic approach was applied, aimed at a theoretical analysis of the development of the concept of demoeconomy components based on demoethical values and consideration of their impact on demographic processes and the transition to “net zero”. Theoretical analysis of the literature made it possible to identify promising directions for the components of demoeconomics. Findings: Based on the value of demoethics, components of the concept of demoeconomics were developed in the context of social cohesion (SC), social responsibility (SR), social justice (SJ), social rationality (SR), social security (SS), which contribute to the achievement of a sustainable transition of a “net zero” and stabilization of demographic processes, increasing the quality of life of the population. Conclusions: The proposed method, together with the demo-economic components of social cohesion (balance), responsibility (SR), justice (SJ), rationality (SR), security (SS), will allow the formation of a strong and competitive civil society. It is also a tool for resolving contradictions during the transition to sustainable development and ensuring the implementation of the Sustainable Development Goals.